Recovery of non-ferrous metals from sulfide ores by bioleaching on the example of the Allarechensk technogenic deposit - Latyuk, E. S.; Goryachev, A. A.; Kompanchenko, A. A. (Vestnik MGTU, 2023)
The possibility of processing sulfide copper-nickel raw materials by heap bioleaching due to the environmental attractiveness of this approach is becoming an increasingly relevant topic for mining and processing. On the example of the Allarechensk technogenic deposit ore, the effectiveness of the bioleaching method for the copper and nickel recovery has been considered. The content of metals in the original ore sample: nickel – 2.42 % and copper – 0.75 %. The ore grinded to the size of –5+3 mm has been irrigated with a solution containing a strain of Acidithiobacillus ferrivorans. The S : L ratio is 4 : 1, the flow rate is equal to 0.1 mL/min. In pregnant solutions, the pH and redox potential values have been controlled, and the concentrations of ferrous and ferric iron, copper, and nickel ions have also been measured. The experiment duration is 11 months, 8.9 % nickel and 6.1 % copper have been recovered. Copper has been extracted from pregnant solutions by cementation on iron, the maximum recovery is 97.3 %. Thus, it has been shown that the proposed scheme for the recovery of metals is promising for the processing of sulfide raw materials, in particular, low-grade ores and enrichment waste.